Does Gender Have an Effect on Craniofacial Measurements? - Lale Taner; Gamze Metin Gürsoy; Fatma Deniz Uzuner (Galenos Yayinevi, 2019)
Objective:The aim of this cross-sectional study was to evaluate craniofacial structures in terms of different sagittal relations and gender in adolescent individuals.Methods:Pre-treatment dental models, lateral cephalometric, and hand-wrist radiographs of 223 adolescent subjects (102 male, 121 female) were evaluated. Subjects were divided into the Angle Class I, II, and III (skeletally) subgroups according to the ANB angle. Four angular and 33 linear measurements were used to evaluate the lateral cephalometric radiographs relative to the R1 and R2 coordinate system. The Kolmogorov-Smirnov test was performed to assess the normal distribution of the data. The independent samples t-test and Mann-Whitney U test were used for the comparison of male and female subjects in each group. The values were considered statistically significant at p<0.05.Results:The vertical facial dimension was found to be significantly greater in Class I male subjects than in female subjects (SGo, p=0.023; ANS-M, p=0.036), and there was a protrusive maxilla (R2ANS, p=0.038; R2A, p=0.016), while the mandibular sagittal position and the mandibular dimension were similar. The maxilla was placed protrusively (R2ANS, p=0.001; R2A, p=0.002), while the mandible was found to be larger both in the position and dimension (CoGn, p=0.003; R2M, p=0.014) in Class II male subjects. Class III male and female subjects were found to have similar maxillary and mandibular vertical and sagittal location and dimensions.Conclusion:Class I and II subjects showed more gender variation than Class III subjects. The gender-related results of this study declare that treatment planning of malocclusions should be based on gender differences rather than general treatment procedures, which will be useful in achieving successful orthodontic treatment results.